Coal and Mineral and its Impact on Human Development Index: An Empirical Study in South and East Kalimantan Region, Indonesia - Hilmawan, Rian; Amalia, Siti (International Journal of Energy Economics and Policy, 2019)
This article aims to analyse the effects of coal and minerals on human development index in South and East Kalimantan Provinces of Indonesia. Historically, Kalimantan was famously known as the largest contributor of coal and mineral production in Indonesia. Under Indonesia's fiscal decentralization policy which effectively ran since 2004, we test: do revenues from coal and minerals negatively affect Human Development Index (HDI)? By focusing on nine coal giant areas within these two provinces that have longer mining histories, and linking it with the coal boom event since the 2000's, and using panel data analysis with fixed effects controlled, we find that coal and mineral revenues have a positive effect on HDI, contrary with resource curse hypothesis. The results remain consistent regardless of inclusion of other important covariates such as the past level of institutional quality and net student enrolment ratio, or whether revenues in all non-renewable resources are used. However, the positive impact found is small in magnitude. For example, for every 10 percentage points increase in the share in coal and mineral revenues in local government budgets, HDI increases by 0.0085 points, ceteris paribus. Keywords: Coal and mineral, Mining, Natural Resources, Human Development Index JEL Classifications: H50, I15, I25, I31 DOI: https://doi.org/10.32479/ijeep.8711